Treating affect phobias: Therapeutic alliance as a moderator of the emotional experience effect on outcomes - Ferreira, Laura Inês (2022)
Psychodynamic-oriented psychotherapies have demonstrated their efficacy in emotional disorders' treatment. However, it remains unclear what are the specific mechanisms accounting for change. In psychodynamic psychotherapeutic models as the Affect Phobia Therapy (APT), emphasis is placed on therapeutic relationship and the ability of clients to regain adaptive contact with their emotions. Specifically, it is argued that there must be a high therapeutic alliance for the emotions' exposure to lead to positive outcomes. This exploratory study aimed to examine whether the level of therapeutic alliance (high vs. low) moderates the contribution of emotional experience to outcomes. Twenty-six clients (65% females; Mage= 25; SD= 7.26) with depressive and/or anxiety symptoms undergoing a psychodynamic psychotherapy on a university counselling centre were included. After each weekly session, clients answered measures of therapeutic alliance, emotional experience, and outcomes (Psychological Well-Being and Subjective Discomfort). Data were analysed using Hierarchical Linear Models for longitudinal data. Results indicated that effect of emotional experience on outcomes depends on levels of therapeutic alliance. In clients with low therapeutic alliance, higher levels of emotional experience contributed to a decrease in Psychological Well-Being and an increase in Subjective Discomfort across sessions. In clients with higher levels of alliance, both outcomes decreased significantly between sessions, regardless of the emotional experience effect. Our findings highlight that it is important to consider that exposure to adaptive emotions may have adverse effects when a strong alliance is not established.